The Effect of Implementing Multimedia-Based Project-Based Learning on the Learning Motivation of 10th-Grade Students in the Islamic Cultural History Course at a State Senior High School - Faqih Abulais; Faridatun Nikmah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
The learning of Islamic Cultural History/Sejarah Kebudayaan Islam (SKI) at MAN 2 Blitar has been monotonous and less motivating for students. This study aims to analyze the effect of implementing Multimedia-based Project Based Learning (PJBL Multimedia) on the learning motivation of tenth-grade students in the SKI subject. A quantitative approach with an ex-post facto design was employed. The research sample consisted of all 35 students of class X-C, taken using total sampling technique. Data were collected through a closed Likert-scale questionnaire that had been tested for validity and reliability, then analyzed using descriptive statistics and simple linear regression. The results show that the implementation of PJBL Multimedia has a significant effect on students' learning motivation with a significance value of 0.000 (<0.05) and a coefficient of determination (R²) of 0.750. The most dominantly affected aspect of motivation is students' belief that learning effort will yield good results (expectancy). It is concluded that PJBL Multimedia is effective in increasing students' learning motivation, particularly through active, constructive, and multimedia-based learning experiences. These findings recommend the use of similar models in teaching SKI and other narrative-contextual subjects.